2009
DOI: 10.7589/0090-3558-45.4.1121
|View full text |Cite
|
Sign up to set email alerts
|

Rabies in Northeastern Europe—the Threat From Invasive Raccoon Dogs

Abstract: ABSTRACT:The red fox (Vulpes vulpes) is the main terrestrial wildlife rabies vector in Europe. However, recently the raccoon dog (Nyctereutes procyonoides)-an invasive species originating from East Asia-has become increasingly important as secondary host, especially in the Baltic States. This imposes problems on neighboring rabies-free countries (such as Finland), where the density of each of the two vector species on its own might be too low to sustain a long-term rabies epizootic, but the community of vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 15 publications
0
47
0
1
Order By: Relevance
“…In a recent simulation study, it is postulated that invasive raccoon dogs, when reaching high density could outcompete native foxes (Singer et al 2009). In Finland, the red fox population started to increase when that of the raccoon dog decreased due to intensive hunting (Kauhala 2004) and female foxes have recently become more carnivorous since the arrival of the raccoon dog (Viranta and Kauhala 2011), indicating potential competition between the two species.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent simulation study, it is postulated that invasive raccoon dogs, when reaching high density could outcompete native foxes (Singer et al 2009). In Finland, the red fox population started to increase when that of the raccoon dog decreased due to intensive hunting (Kauhala 2004) and female foxes have recently become more carnivorous since the arrival of the raccoon dog (Viranta and Kauhala 2011), indicating potential competition between the two species.…”
Section: Discussionmentioning
confidence: 98%
“…The raccoon dog is also known to be an important reservoir host of Trichinella spp. (Bružinskaitė-Schmidhalter et al 2012; Kauhala and Kowalczyk 2011; Thiess et al 2001) and has been identified as important rabies vector in northeastern Europe (Holmala and Kauhala 2006; Singer et al 2009). Due to broad oral vaccination campaigns, rabies is of less relevance in central Europe and is known to be eradicated in Austria since 2008 (Hirk et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With strong efforts from Poland and other eastern European countries, the rabies-free zone has been expanded further to the east (Matouch et al 2007;Cliquet et al 2010). However, pockets of endemic wildlife rabies still remain in countries such as Russia, the Baltic States, and Belarus (Singer et al 2009). The reasons for the persistence of rabies-positive foci include the high cost of vaccination campaigns, and the presence of other rabies vectors, which can make rabies control efforts more challenging in areas such as the Baltic States (Singer et al 2009).…”
mentioning
confidence: 99%
“…However, pockets of endemic wildlife rabies still remain in countries such as Russia, the Baltic States, and Belarus (Singer et al 2009). The reasons for the persistence of rabies-positive foci include the high cost of vaccination campaigns, and the presence of other rabies vectors, which can make rabies control efforts more challenging in areas such as the Baltic States (Singer et al 2009). While the red fox (Vulpes vulpes) remains the main rabies vector in Western Europe, the Raccoon dog (Nyctereutes procyonoides) and the arctic fox (Alopex vulpes) play an important role in the chain of infection in Eastern and Northern Europe (Wandeler 2008).…”
mentioning
confidence: 99%